Short‐Term Outcomes of Acute Stroke During COVID‐19 by Race and Ethnicity in the United States: The Society of Vascular and Interventional Neurology Multicenter Collaboration - Alicia M. Zha; Anjail Z. Sharrief; Alexandra L. Czap; David S. Liebeskind; Nirav Vora; Vivek Rai; Shashvat Desai; Ashutosh P. Jadhav; Italo Infante; Amy Starosciak; Ameer Hassan; Mudassir Farooqui; et al. (Stroke: Vascular and Interventional Neurology, 2022)
Background The COVID‐19 pandemic has disproportionately affected Black and Hispanic communities, whose stroke care has been previously shown to experience existing disparities. We sought to evaluate how these disparities in stroke care and in‐hospital mortality have been affected by the COVID‐19 pandemic. Methods In this retrospective observational cohort study, we evaluated stroke hospitalizations in the Society of Vascular and Interventional Neurology COVID‐19 registry. We compared stroke characteristics between non‐Hispanic White, non‐Hispanic Black, and Hispanic patients pre–COVID‐19 and post–COVID‐19 (March–July 2019 versus March–July 2020) and evaluated whether racial and ethnic differences present before the pandemic were exacerbated during the pandemic. Our primary outcome was in‐hospital mortality/discharge to hospice, and secondary outcomes were acute treatment use. Results Of the 4908 included patients, numerically fewer non‐Hispanic White and Hispanic patients were evaluated during COVID‐19. Non‐Hispanic White and non‐Hispanic Black patients with large‐vessel occlusion were more likely to undergo thrombectomy (P<0.01 for both) when compared with the pre–COVID‐19 epoch. In‐hospital mortality/hospice rates were higher during COVID‐19 (12.8% versus 9.9%; P<0.01), with higher rates observed across all race and ethnic groups, although the odds of death/hospice during the pandemic period became nonsignificant after multivariable adjustment (adjusted odds ratio, 1.23 [95% CI, 0.95–1.62]; P=0.12). Conclusions There was an increase in mortality/hospice discharges among all races during the COVID‐19 period. There were no noted racial or ethnic differences in rates of thrombolytic use, thrombectomy, or mortality within racial groups prepandemic compared with during the pandemic. Although other studies have demonstrated deepening disparities in these outcomes during COVID‐19, our data suggest that declines in stroke presentations and use of acute stroke therapies were not a uniform phenomenon. Disparities in stroke care were differentially affected in thrombolytic versus endovascular therapies and among non‐Hispanic Black and Hispanic patients.